Thermodynamics of RNA duplexes modified with unlocked nucleic acid nucleotides - Pasternak, Anna (Oxford University Press, 2010)
Thermodynamics provides insights into the influence of modified nucleotide residues on stability of nucleic acids and is crucial for designing duplexes with given properties. In this article, we introduce detailed thermodynamic analysis of RNA duplexes modified with unlocked nucleic acid (UNA) nucleotide residues. We investigate UNA single substitutions as well as model mismatch and dangling end effects. UNA residues placed in a central position makes RNA duplex structure less favourable by 4.0–6.6 kcal/mol. Slight destabilization, by ∼0.5–1.5 kcal/mol, is observed for 5′- or 3′-terminal UNA residues. Furthermore, thermodynamic effects caused by UNA residues are extremely additive with ΔG°(37) conformity up to 98%. Direct mismatches involving UNA residues decrease the thermodynamic stability less than unmodified mismatches in RNA duplexes. Additionally, the presence of UNA residues adjacent to unpaired RNA residues reduces mismatch discrimination. Thermodynamic analysis of UNA 5′- and 3′-dangling ends revealed that stacking interactions of UNA residues are always less favourable than that of RNA residues. Finally, circular dichroism spectra imply no changes in overall A-form structure of UNA–RNA/RNA duplexes relative to the unmodified RNA duplexes.